Yellow light wave band derived glass optical fiber based on Dy: YAG transparent ceramic and preparation method of yellow light wave band derived glass optical fiber
By using DY: YAG transparent ceramics as a fiber core and quartz glass bag layer, the yellow light wave band DY: YAG derivative glass fiber, solved the limitations of the existing DY3+doped fluoride glass fiber in yellow light laser output performance, realized realization The effect of low transmission loss and low loss with commercial quartz fiber.
Patent Information
- Application Number
- CN202411494326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
AI Technical Summary
The existing Dy3+ doped fluoride glass fibers have limitations in yellow laser output performance, including poor chemical stability, low laser damage threshold, poor gain performance, and difficulty in low loss welding with commercial quartz fibers.
Using DY: YAG transparent ceramics as a fiber core, combined with quartz glass packs, prepare the yellow light wave band DY: YAG derivative glass fiber through high temperature pull-ups, achieved a complete core-packaging structure and low transmission loss.
The low transmission loss (the yellow light wave segment loss is less than 0.2DB/cm) and the molten losses of low losses with commercial quartz fiber (fusion loss less than 0.3DB), and at the same time have excellent laser performance and wide applicability.
Smart Images

Figure CN119376008A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical fibers, and in particular relates to a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramics and a preparation method thereof. Background Art
[0002] Visible yellow lasers with a wavelength range of about 565-590nm are widely used in laser medical treatment, laser radar, astronomical observation, etc. For example, yellow lasers with a wavelength of 589nm with high power, narrow linewidth and high beam quality can be used in adaptive optics technology in astronomical telescopes. Compared with traditional bulk solid lasers, fiber lasers have the advantages of good heat dissipation performance, high degree of integration, good stability and high conversion efficiency. Among them, the use of laser diodes (LD) to pump rare earth-doped optical fiber materials can directly realize yellow light transmission, and the yellow light laser can be output after resonant cavity mode selection and amplification. This direct emission method can eliminate the traditional complex nonlinear optical process and has the advantages of simple system, low loss and high reliability.
[0003] At present, the mainstream gain fiber for direct output of yellow laser is Dy-doped 3+ Fluoride glass fiber (Electronics Lettres, 2000, 36 (16): 1386-1387; Solid State Lasers XX: Technology and Devices, 2011, 7912: 79120J; Optics Letters, 2019, 44 (17): 4423-4426; Optics Letters, 2022, 47 (5): 1157-1160; Photonics Research, 2021, 9 (4), 446-451.). The lower phonon energy of fluoride glass fiber is conducive to the realization of yellow light laser output, but on the one hand, the relatively poor chemical stability and low laser damage threshold of fluoride glass greatly hinder the development of Dy 3+ The output power of the doped yellow fiber laser is improved; secondly, the softening temperature, expansion coefficient and other properties of fluoride glass and quartz glass are quite different, making it difficult to achieve low-loss welding with commercial quartz fiber; in addition, the fluoride ion radius in fluoride glass is small, the polarizability is low, and the covalency to the surrounding local field is small, resulting in Dy 3+ The Ω2 value is small, and the fluorescence branching in the yellow light band is relatively low, which leads to a low emission cross section of yellow light emission and poor gain performance. In addition to fluoride glass fibers, there are also a few Dy 3+There are reports on doping other glass fibers, such as traditional SiO2 fibers and phosphate fibers (OSA Continuum, 2021, 4(11), 2845-2851; Applied Physics Express, 2022, 15(1): 012002; Journal of Non-Crystalline Solids 2022, 577.), but due to the low solubility of rare earth ions in these traditional glass fibers, the gain effect needs to be further improved; in addition, there is Dy 3+ Doped microcrystalline composite glass optical fiber (Nanomaterials, 2023, 13 (9): 1558; Optical Materials Express 2024, 14 (8): 2023-2031.), but the existing technology has not yet completely solved the effect of nanocrystal size on optical fiber transmission loss, so there is still no breakthrough in Dy 3+ With the progress of fluoride-doped glass fiber in yellow laser output performance, researchers have been committed to finding new alternative materials.
[0004] YAG is a widely applicable laser crystal with advantages such as high mechanical properties, good thermal conductivity, and can be used for high repetition rate and continuous output. By placing doped YAG material in a quartz cladding, different YAG-derived optical fibers can be drawn. In the prior art, the core precursor for preparing doped YAG-derived optical fibers generally includes: (1) doped YAG single crystal. For example, patent CN109085674 A discloses a 2-micron band single crystal derived all-glass optical fiber and its preparation method. In addition, there are related research reports such as (Optical Materials, 2012, 34 (8), 1294-1298; Ceramics International., 2017, 43, 5837-5841; Optics Letters, 2023, 48 (19): 5109-5112; Optical Materials Express, 2021, 11 (10): 3587-3599). However, this method is very unfavorable for industrial production due to the complicated crystal preparation process and high production cost; (2) Rare earth doped YAG powder. For example, Journal of the American Ceramic Society. 2022, 105 (12), 7064-7071 reported that the powder core with low packing density leads to problems such as bubble residue, resulting in high optical fiber transmission loss, affecting the gain performance of the optical fiber, and may even cause the optical fiber to break during preparation or use. There is no report on related improvement technology. In addition, the existing technology on rare earth doped YAG derived glass optical fiber research is only in the infrared band, and there is no report on YAG derived optical fiber in the yellow light band. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramics and a preparation method thereof. This method combines the advantages of the excellent laser performance of Dy:YAG transparent ceramics and the good flexibility and low laser threshold of optical fibers, uses Dy:YAG transparent ceramics with high density, few defects and low production cost as the fiber core, and uses quartz glass as the cladding to prepare a yellow light band Dy:YAG derived glass optical fiber through high-temperature drawing. The Dy:YAG derived glass optical fiber obtained by the present invention has a complete core-cladding structure, low transmission loss, and can be fused with commercial quartz optical fiber at low loss. The preparation process of the present invention has wide applicability and solves the current Dy:YAG derivative glass optical fiber. 3+ The problem that doped glass optical fiber cannot achieve excellent gain performance, stable transmission performance and low-loss fusion with commercial quartz optical fiber can be solved by Dy 3+ Doped yellow fiber lasers provide excellent luminescence and a stable gain medium.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] A yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic, the cladding of the optical fiber is quartz glass, and the optical fiber core is Dy 3+ Doped Y3Al5O 12 The fiber core precursor is Dy:YAG transparent ceramic that can emit in the yellow light band.
[0008] Further preferably, the Dy 3+ The chemical formula of doped YAG transparent ceramic is Y 3-x Al5O 12 :xDy 3+ , x=0.02~0.08.
[0009] Further preferably, the core diameter of the Dy:YAG derived glass optical fiber is 5-20 μm, and the outer diameter of the cladding is 120-130 μm, which are standard optical fiber dimensions.
[0010] Further preferably, the Dy:YAG derived glass optical fiber obtains broadband yellow light emission under the pumping of a blue light semiconductor laser, and its ASE spectrum ranges from 550 to 600 nm; and is low-loss fused with commercial quartz optical fiber, and the fusion loss is less than 0.3 dB; and the transmission loss in the yellow light band is less than 0.2 dB / cm.
[0011] A method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramics comprises the following steps:
[0012] (1) cleaning the quartz glass tube with dilute hydrochloric acid and anhydrous ethanol having a volume concentration of less than or equal to 5 vol.%, and then drying it in a drying oven;
[0013] (2) using an oxyhydrogen flame gun to perform taper sealing on one end of the quartz glass tube;
[0014] (3) placing Dy:YAG transparent ceramics of matching size in a quartz glass tube to obtain an optical fiber preform; (4) drawing the optical fiber preform in a vacuum high-temperature graphite furnace at a high temperature of 1980 to 2030° C. to obtain a Dy:YAG derived glass optical fiber.
[0015] More preferably, the outer diameter of the preform quartz tube in step (1) is 20-30 mm, the inner diameter is 3-5 mm, and the length is 15-20 cm. The diameter of the transparent ceramic core precursor in step (3) is 2.8-4.8 mm, and the length is 3-5 cm.
[0016] Further preferably, the optical fiber drawing process in step (4) is protected by argon gas. During the high-temperature drawing process, the molten core (the melting point of Dy:YAG transparent ceramic is 1800°C) is filamented together with the softened cladding quartz glass, and then rapidly cooled to room temperature to obtain a continuous Dy 3+ Doped YAG transparent ceramic-derived glass optical fiber;
[0017] Preferably, the yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic is characterized in that the core diameter of the Dy:YAG derived glass optical fiber is 5 to 20 μm, and the outer diameter of the cladding is a standard optical fiber size of about 120 to 130 μm.
[0018] Preferably, the yellow light band derived glass optical fiber prepared based on Dy:YAG transparent ceramic is characterized in that the Dy:YAG derived glass optical fiber can obtain broadband yellow light emission under the pumping of a blue light semiconductor laser, and its ASE spectrum range is 550-600nm. It can be low-loss fused with commercial quartz optical fiber, and the fusion loss is less than 0.3dB; the transmission loss in the yellow light band is less than 0.2dB / cm.
[0019] Due to the adoption of the above technical solution, the present invention has the following outstanding features and positive effects compared with the prior art:
[0020] (1) The Dy:YAG derived glass optical fiber in the yellow light band of the present invention fully combines the advantages of excellent laser performance of Dy:YAG transparent ceramics and good flexibility and low laser threshold of optical fibers. With Dy:YAG transparent ceramics with high density and few defects as the fiber core, the optical fiber can be drawn by a core melting method using a commercial optical fiber drawing tower. The obtained Dy:YAG derived glass optical fiber has a complete core-clad structure and low transmission loss (loss is less than 0.2dB / cm in the yellow light band).
[0021] (2) The yellow light band Dy:YAG derived glass optical fiber of the present invention has a cladding of quartz glass. Compared with other multi-component glass optical fibers such as fluoride, phosphate, and germanate, it has good compatibility with existing commercial quartz optical fiber systems and can achieve a fusion loss of less than 0.3 dB.
[0022] (3) The present invention provides a method for preparing a yellow light band Dy:YAG derived glass optical fiber, wherein the fiber core adopts Dy:YAG transparent ceramics, which can ensure excellent laser properties. At the same time, compared with similar single crystals, the preparation process has low technical requirements and wide adaptability, which can save costs and improve production efficiency.
[0023] (4) The yellow light band Dy:YAG derived glass optical fiber of the present invention can be used in yellow light fiber lasers as a high-performance and stable gain medium. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the ASE spectrum of the yellow light band Dy:YAG derived glass optical fiber prepared in Example 2 of the present invention.
[0025] Figure 2 This is an optical microscopic picture of the cross section of the yellow light band Dy:YAG derived glass optical fiber prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but is not intended to limit the scope of protection thereof.
[0027] The quartz glass tube used in the embodiment is treated as follows: the quartz glass tube is cleaned with dilute hydrochloric acid and anhydrous ethanol with a volume concentration of less than or equal to 5 vol.%, and then dried in a drying oven, and then one end of the quartz glass tube is tapered and sealed with a hydrogen-oxygen flame gun.
[0028] Example 1
[0029] 0.02Dy 3+ :Y 2.98 Al5O 12The transparent ceramic rod was ground into a cylinder with a diameter of 3.8 mm and a length of 4 cm, and the core ceramic rod was placed in a quartz glass tube with an inner diameter of 4 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform; the preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 1980°C. The core diameter of the optical fiber was 10 μm and the outer diameter of the cladding was 130 μm. The emission spectrum of the derived glass fiber was tested using an Ocean Maya2000 Pro fiber spectrometer. The excitation source was a 450nm semiconductor laser, and broadband yellow light emission was obtained. Its ASE spectrum range was 550-600nm. The transmission loss of the derived optical fiber was measured by the truncation method to be 0.15 dB / m. The derived optical fiber was fused with a commercial quartz optical fiber using a fiber fusion splicer, and the fusion loss was 0.22 dB. The above results show that the optical fiber can be used in yellow light fiber lasers and can be used as a high-performance and stable gain medium.
[0030] Example 2
[0031] 0.05Dy 3+ :Y 2.95 Al5O 12 The transparent ceramic rod was ground into a cylinder with a diameter of 2.8 mm and a length of 3 cm, and the core ceramic rod was placed in a quartz glass tube with an inner diameter of 3 mm, an outer diameter of 25 mm and a length of 15 cm to obtain an optical fiber preform; the preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2010°C, which is higher than the melting temperature of the core material. The core diameter of the optical fiber is 5 μm and the outer diameter of the cladding is 125 μm. The ASE emission spectrum of the derived glass optical fiber was tested using the Ocean Maya2000 Pro fiber spectrometer, and the excitation source was a 450nm semiconductor laser. Figure 1 As shown in the figure, the Dy:YAG derived glass fiber has a fluorescence branching ratio of 80% in the yellow light band, its ASE spectrum range is 550-600nm, and its luminescence intensity increases with the increase of pump power. The transmission loss of the derived fiber measured by the truncation method is 0.10dB / m. The derived fiber is fused with commercial quartz fiber using a fiber fusion splicer, and the fusion loss is 0.15dB. The above results show that the fiber can be used in yellow light fiber lasers as a high-performance and stable gain medium.
[0032] Example 3
[0033] 0.06Dy 3+ :Y 2.94 Al5O 12The transparent ceramic rod was ground into a cylinder with a diameter of 4.8 mm and a length of 5 cm, and the core ceramic rod was placed in a quartz glass tube with an inner diameter of 5 mm, an outer diameter of 30 mm, and a length of 20 cm to obtain an optical fiber preform; the preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2020°C, which is higher than the melting point of the core material. The core diameter of the optical fiber is 6 μm and the outer diameter of the cladding is 125 μm. The emission spectrum of the derived glass optical fiber was tested using an Ocean Maya2000 Pro fiber spectrometer. The excitation source was a 450nm semiconductor laser to obtain broadband yellow light emission, and its ASE spectrum range was 550-600nm. The transmission loss of the derived optical fiber was measured by the truncation method to be 0.11 dB / m. The derived optical fiber was fused with a commercial quartz optical fiber using a fiber fusion splicer, and the fusion loss was less than 0.16 dB. The cross-sectional optical micrograph of the Dy:YAG derived glass optical fiber prepared in Example 3 is shown in the following figure. Figure 2 As shown, from Figure 2 It can be seen that the fiber has a complete core-cladding structure and the interface contact between the core and the cladding is good. The above results show that the fiber can be used in yellow light fiber lasers as a high-performance and stable gain medium.
[0034] Example 4
[0035] 0.08Dy 3+ :Y 2.92 Al5O 12 The transparent ceramic rod was ground into a cylinder with a diameter of 4.8mm and a length of 5cm, and the core ceramic rod was placed in a quartz glass tube with an inner diameter of 5mm, an outer diameter of 25mm and a length of 15cm to obtain an optical fiber preform; the preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2000℃, which is higher than the melting temperature of the core material. The core diameter of the optical fiber is 20μm and the outer diameter of the cladding is 127μm. The emission spectrum of the derived glass fiber was tested using an Ocean Maya2000 Pro fiber spectrometer. The excitation source was a 450nm semiconductor laser, and broadband yellow light emission was obtained. Its ASE spectrum range was 550-600nm. The transmission loss of the derived optical fiber was measured by the truncation method to be 0.19dB / m. The derived optical fiber was fused with a commercial quartz optical fiber using a fiber fusion splicer, and the fusion loss was 0.29dB. The above results show that the optical fiber can be used in yellow light fiber lasers and can be used as a high-performance and stable gain medium.
[0036] Example 5
[0037] 0.04Dy 3+ :Y 2.96 Al5O 12The transparent ceramic rod was ground into a cylinder with a diameter of 3.8mm and a length of 4cm, and the core ceramic rod was placed in a quartz glass tube with an inner diameter of 4mm, an outer diameter of 25mm and a length of 15cm to obtain an optical fiber preform; the preform was then placed in a vacuum high-temperature graphite furnace and drawn into an optical fiber at a high temperature of 2030℃, which is higher than the melting temperature of the core material. The core diameter of the optical fiber is 10μm and the outer diameter of the cladding is 120μm. The emission spectrum of the derived glass fiber was tested using an Ocean Maya2000 Pro fiber spectrometer. The excitation source was a 450nm semiconductor laser, and broadband yellow light emission was obtained. Its ASE spectrum range was 550-600nm. The transmission loss of the derived optical fiber was measured by the truncation method to be 0.12dB / m. The derived optical fiber was fused with a commercial quartz optical fiber using a fiber fusion splicer, and the fusion loss was 0.20dB. The above results show that the optical fiber can be used in yellow light fiber lasers and can be used as a high-performance and stable gain medium.
[0038] The above embodiments are preferred implementation methods of the present invention, but the implementation methods of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic, characterized in that: The cladding of the optical fiber is quartz glass, and the core of the optical fiber is Dy 3+ Doped Y3Al5O 12 The glass body is derived from transparent ceramics, and the core precursor is Dy:YAG transparent ceramic that can achieve yellow light band emission.
2. The yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 1, characterized in that: The Dy 3+ Doped Y3Al5O 12 The chemical formula of transparent ceramic is Y 3-x Al5O 12 :xDy 3+ , x=0.02~0.
08.
3. The yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 1, characterized in that: The core diameter of the Dy:YAG derived glass optical fiber is 5-20 μm, and the outer diameter of the cladding is 120-130 μm, which is a standard optical fiber size.
4. The yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 1, characterized in that: The Dy:YAG derived glass optical fiber obtains broadband yellow light emission under the pumping of a blue light semiconductor laser, and its ASE spectrum range is 550-600nm.
5. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramics according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Cleaning the quartz glass tube with dilute hydrochloric acid and anhydrous ethanol in sequence, and then drying it in a drying oven; (2) using an oxyhydrogen flame gun to perform taper sealing on one end of the quartz glass tube; (3) placing Dy:YAG transparent ceramics of matching size in a quartz glass tube to prepare an optical fiber preform; (4) Drawing the optical fiber preform in a vacuum high-temperature graphite furnace at high temperature to obtain a Dy:YAG derived glass optical fiber.
6. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 5, characterized in that: In step (1), the volume concentration of the dilute hydrochloric acid is less than or equal to 5 vol.%.
7. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 5, characterized in that: In step (1), the quartz glass tube has an outer diameter of 20 to 30 mm, an inner diameter of 3 to 5 mm, and a length of 15 to 20 cm.
8. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 5, characterized in that: In step (3), the transparent ceramic core precursor has a diameter of 2.8 to 4.8 mm and a length of 3 to 5 cm.
9. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 5, characterized in that: In step (4), the drawing process is protected by argon gas. During the high-temperature drawing process, the molten core is formed into a filament together with the softened cladding quartz glass, and then quickly cooled to room temperature to obtain a continuous Dy 3+ Doped YAG transparent ceramic-derived glass optical fiber.
10. The method for preparing a yellow light band derived glass optical fiber based on Dy:YAG transparent ceramic according to claim 5, characterized in that: In step (4), the high temperature is 1980-2030°C.
Citation Information
Patent Citations
Full glass fiber derived from 2-micron band single crystal and preparation method thereof
CN109085674A